Spatial and Temporal Patterns of Pore Water Chemistry in the Inter-Tidal Zone of a High Energy Beach - Waska, Hannelore; Greskowiak, J.; Ahrens, J.; Beck, M.; Ahmerkamp, S.; Böning, P.; Brumsack, H. J.; Degenhardt, J.; Ehlert, C.; Engelen, B.; Grünenbaum, N.; Holtappels, M.; et al. (Frontiers in Marine Science, 2019)
Submarine groundwater discharge (SGD) is a ubiquitous source of meteoric fresh groundwater and recirculating seawater to the coastal ocean. Due to the hidden distribution of SGD, as well as the hydraulic- and stratigraphy-driven spatial and temporal heterogeneities, one of the biggest challenges to date is the correct assessment of SGD-driven constituent fluxes. Here, we present results from a 3-dimensional seasonal sampling campaign of a shallow subterranean estuary in a high-energy, meso-tidal beach, Spiekeroog Island, Northern Germany. We determined beach topography and analyzed physico-chemical and biogeochemical parameters such as salinity, temperature, dissolved oxygen, Fe(II) and dissolved organic matter fluorescence (FDOM). Overall, the highest gradients in pore water chemistry were found in the cross-shore direction. In particular, a strong physico-chemical differentiation between the tidal high water and low water line was found and reflected relatively stable in- and exfiltrating conditions in these areas. Contrastingly, in between, the pore water compositions in the existing foreshore ridge and runnel system were very heterogeneous on a spatial and temporal scale. The reasons for this observation may be the strong morphological changes that occur throughout the entire year, which affect the exact locations and heights of the ridge and runnel structures and associated flow paths. Further, seasonal changes in temperature and inland hydraulic head, and the associated effect on microbial mediated redox reactions likely overprint these patterns. In the long-shore direction the pore water chemistry varied less than the along the cross-shore direction. Variation in long-shore direction was probably occurring due to topography changes of the ridge-runnel structure and a physical heterogeneity of the sediment, which produced non-uniform groundwater flow conditions. We conclude that on meso-tidal high energy beaches, the rapidly changing beach morphology produces zones with different approximations to steady-state conditions. Therefore, we suggest that zone-specific endmember sampling is the optimal strategy to reduce uncertainties of SGD-driven constituent fluxes.